Factor of Deficiencies In Insurance Sector: Examining the Impact of Gender, Marital Status, Education, Income, and Periodicity on Policy Holder Satisfaction in the Insurance Sector (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Gender, marital status, education, income and periodicityof  premium  exerted significant  impact  on  the  level of  satisfaction  of policy holders  in  insurance sector.  Female  and married  policy  holders were  found  be more satisfied than male and unmarried policy holders on the performanceof a company. Enhancement  in  education and  income  raise the  expectations  of policy  holders,  hence lowering down their level ofsatisfaction. Longer periodicity results in enhanced level of satisfaction.Therefore, it is advisable that the insurance companies should evolve suitablepolicies to raise the satisfaction level of their customers.